Continuous versus intermittent running: acute performance decrement and training load - Kesisoglou, A.; Nicolò, A.; Howland, L.; Passfield, L. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To examine the effect of continuous (CON) and intermittent (INT) running training sessions of different durations and intensities on subsequent performance and calculated training load (TL).